2004
DOI: 10.1002/ejic.200400236
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Study of Bisphosphonate Metal Complexes − Three New Polymeric Structures of the Calcium Complex of Clodronic Acid

Abstract: Three novel calcium complexes of clodronic acid were prepared and their structures determined by single‐crystal X‐ray diffractometry. Previously, a monomeric structure, [Ca{Cl2C(PO3H)2}(H2O)5] (1), has been determined, but the new structures are polymeric: [{Ca2[Cl2C(PO3)2](H2O)6}·4.5H2O]n (2), [{Ca2Na0.5[Cl2C(PO3)2](H2O)8}Cl0.5·4H2O]n (3) and [{Ca5[Cl2C(PO3)2]2(H2O)15}(NO3)2·1.5H2O]n (4); and they provide new, important information about the binding abilities of clodronic acid. Compounds 2−4 crystallise in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…The coordination mode of Ca 2+ is different in polymeric structures of bound clodronate complexes than in the monomeric analogues. [{Ca 2 [Cl 2 C(PO 3 ) 2 ](H 2 O) 6 }⋅4.5H 2 O] n ( 1 ) (Figure ), [{Ca 2 Na 0.5 [Cl 2 C(PO 3 ) 2 ](H 2 O) 8 }Cl 0.5 ⋅4 H 2 O] n ( 2 ), and [{Ca 5 [Cl 2 C(PO 3 ) 2 ] 2 (H 2 O) 15 }(NO 3 ) 2 ⋅1.5 H 2 O] n ( 3 ) revealed that ligands provide seven oxygen donor atoms: four arising from bisphosphonate units and the remaining sites are occupied by water molecules. The geometry is a distorted mono‐capped trigonal prism.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The coordination mode of Ca 2+ is different in polymeric structures of bound clodronate complexes than in the monomeric analogues. [{Ca 2 [Cl 2 C(PO 3 ) 2 ](H 2 O) 6 }⋅4.5H 2 O] n ( 1 ) (Figure ), [{Ca 2 Na 0.5 [Cl 2 C(PO 3 ) 2 ](H 2 O) 8 }Cl 0.5 ⋅4 H 2 O] n ( 2 ), and [{Ca 5 [Cl 2 C(PO 3 ) 2 ] 2 (H 2 O) 15 }(NO 3 ) 2 ⋅1.5 H 2 O] n ( 3 ) revealed that ligands provide seven oxygen donor atoms: four arising from bisphosphonate units and the remaining sites are occupied by water molecules. The geometry is a distorted mono‐capped trigonal prism.…”
Section: Introductionmentioning
confidence: 99%
“…[59] Within this group, the greatest number of studies have been devoted to etidronate [42,[66][67][68][69][70][71][72][73][74] and clodronate. [67,69,[75][76][77][78][79] Others, such as pamidronate, [59,72,80] alendronate, [59,72,81] tiludronate, [82] or zolendronate [83,84] have been discussed in only af ew research papers. To the best of the author's knowledge,o riginal data for risedronate and ibandronate directly binding to Ca 2 + are not available to date.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations